TINJAUAN YURIDIS TERHADAP PUTUSAN PENGADILAN TATA USAHA NEGARA SAMARINDA NOMOR : 52/G/2019/PTUN.SMD TENTANG PEMBERHENTIAN TIDAK DENGAN HORMAT SEBAGAI PEGAWAI NEGERI SIPIL KARENA MELAKUKAN TINDAK PIDANA KORUPSI - Vinzensia Nella Bannerara (Universitas 17 Agustus 1945 Samarinda, 2019)
AbstractCivil servants in carrying out their duties and roles as state servants are not impossible to commit an offense, in this case committing a criminal act of corruption which as a result is dishonorably discharged as a civil servant based on a state administrative decree, disrespectful dismissal as a civil servant must provide legal certainty if not, it will result in the creation of employment disputes between PNS and State Administrative Officials who are the authority of the State Administrative Court to settle claims from PNS. The problem in this research is whether the basis for civil servants filing a lawsuit for disrespectful dismissal for committing a criminal act of corruption and what factors are considered by the judge in granting the lawsuit Number: 52 / G / 2019 / PTUN.SMD.The method used in this research is the normative juridical research method.Based on the results of the research, the basis for the birth of a lawsuit against disrespectful dismissal as a civil servant is that the application or implementation of dismissal is not appropriate with the applicable rules and the judge's consideration in granting a lawsuit is that the procedure for issuing a letter of disrespectful dismissal as a civil servant is not in accordance with statutory regulations and defects in substance so that it is contrary to the proportional element and justice does not reflect the general principles of good governance, especially the principles of legal certainty, the principles of justice and the principles of accuracy.